Impact of Exports on Economic Growth- A Case of Luxemburg - Usman, Muhammad; ., Hafiz Waqas Kamran; ., Hassan Khalid (Information Management and Business Review, 2012)
The key purpose of this article is to analyze the significant impact of Exports, Government expenditures and Education expenditures on the economic growth of the developed economy of the Luxemburg, which is the member state of the EU: the biggest exporter in the world. The span of time is from the year 1975 to 2009 on yearly basis with total no. of observations of 35. Present analysis is based on the simple ordinary least square method to indentify the important linkage between the export and the growth considering the economy of Luxemburg. Experimental results reveal a significant positive relationship of exports, government spending, educational expenditure, on growth of the economy. Export shows that one unit increase in the export cause a positive change of .17 in the economic growth. In the same way government, exp. and education exp. show a coefficient of 2.67 and 9.93 with positive sign. This article identifies the association between the export and the economic growth with respect to Luxemburg.